A framework for chronic care quality: results of a scoping review and Delphi survey - Grace Marie V. Ku; Willem Van De Put; Deogratias Katsuva; Mohamad Ali Ag Ahmed; Megumi Rosenberg; Bruno Meessen (Global Health Action)
Frameworks conceptualising the quality of care abound and vary; some concentrate on specific aspects such as safety, effectiveness, others all-encompassing. However, to our knowledge, tailoring to systematically arrive at a comprehensive care for chronic conditions quality (CCCQ) framework has never been done. We conducted a scoping review and Delphi survey to produce a CCCQ framework, comprehensively delineating aims, determinants and measurable attributes. With the assumption that specific groups (people with chronic conditions, care providers, financiers, policy-makers, etc.) view quality of care differently, we analysed 48 scientific and 26 grey literature deductively and inductively using the Institute of Medicine’s quality of care framework as the foundation. We produced a zero-version of the quality of chronic care framework, detailing aims, healthcare system determinants, and measurement mechanisms. This was presented in a Delphi survey to 49 experts with diverse chronic care expertise/experience around the world. Consensus was obtained after the first round, with the panel providing suggestions and justifications to expand the agreed-upon components. Through this exercise, a comprehensive CCCQ framework encompassing the journey through healthcare of people with chronic conditions was developed. The framework specifies seven CCCQ ‘aims’ and identifies health system determinants which can be acted upon with ‘organising principles’ and measured through chronic care quality ‘attributes’ related to structures, processes and outcomes. Tailoring quality of care based on the nature of the diseases/conditions and considering different views can be done to ensure a comprehensive offer of healthcare services, and towards better outcomes that are acceptable to both the health system and people with chronic conditions (PwCC).